Biological and biochemical modulation of DNA methylation. (December 2014) - Lo, Raymond; Weksberg, Rosanna
Epigenetic regulation is facilitated by a battery of proteins that act as 'writers' or 'erasers' to add or remove biochemical modifications to DNA and histone proteins. DNA modifications, histone modifications and long noncoding RNAs function interdependently through reciprocal crosstalk. This review will focus on DNA methylation and DNA methyltransferases with emphasis on how biological and biochemical factors such as histone modifications and noncoding RNAs might play a role in modulating DNA methylation. Other physiological and biochemical factors that can modify DNA methylation marks will also be discussed including chemical exposures and inflammation.